Predictor factor on relapse among former addicts - Razali, Asbah; Madon, Zainal (Human Resource Management Academic Research Society, 2020)
The inclination to relapse among drug addicts is related to the desire of former addicts to relapse drugs after the end of their treatment and rehabilitation process. Identifying the predictor factor for the inclination to relapse among former addicts could not only prevent relapse, but also recognise the largest influence in their lives that contribute to their relapse. This study uses the questionnaires of the Inventory of Drug-Taking Situations, General Self Efficacy, Coping Strategy and Social Provisions Scale. The findings show there are six identifiable significant predictor variables and the main contributors to the inclination to relapse; problem-focused coping, emotion-focused coping, avoidance coping, self-efficacy, family support, and peer support towards the inclination to relapse. Based on the results, it could be concluded that these six predictor variables have been identified as significant and the main contributors to the inclination to relapse. The findings also found self-efficacy to have a significant effect on the inclination to relapse. This study could indirectly aid the government in their efforts to overcome the drug problem, and benefit the affected parties in formulating various rehabilitation and prevention programmes for former addicts, as failure to solve this problem not only threatens the lives of individuals, but also the national social and economic development.